2016
DOI: 10.1590/1809-4422asoc150111r1v1912016
|View full text |Cite
|
Sign up to set email alerts
|

Water crisis in São Paulo: news coverage, public perception and the right to information

Abstract: Based on materials published by different media outlets on the coverage of water crisis which affected the region of São Paulo in 2014 and on the concept of publizistikwissenschaft, this article seeks to evaluate the process of information construction in the public sphere. It appears that major media outlets embraced 'news' frameworks, while smaller and independent media adopted 'interpretative' frameworks. The former emphasized the problem of climate change and issues related to water consumption, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Within the hypothesis constructed in this study, these barriers can function as detractors of the organizational climate, moving the individual away from his sense of social responsibility, effectiveness and belonging in the institution's decision-making process. Martirani and Peres (2016) observed that the analysis of the water crisis in São Paulo also undergoes conflicting communication and with little social control, reporting the socioenvironmental conflicts involving private interests and collective benefits, observed in the divergences between the Brazilian Forest Code itself and the National Water Resources Policy, which defines water as a public good and recommends a decentralized management process, guided by environmental governance, with the participation of public authorities, users and communities, aiming at strengthening the committees, including in the decision-making processes. Silva et al (2016) reported that, although legally ensured, transparency and social control in public health are often not observed in a practical way, and that many public sector contracts with private service providers are not properly presented to interested citizens.…”
Section: Figurementioning
confidence: 99%
“…Within the hypothesis constructed in this study, these barriers can function as detractors of the organizational climate, moving the individual away from his sense of social responsibility, effectiveness and belonging in the institution's decision-making process. Martirani and Peres (2016) observed that the analysis of the water crisis in São Paulo also undergoes conflicting communication and with little social control, reporting the socioenvironmental conflicts involving private interests and collective benefits, observed in the divergences between the Brazilian Forest Code itself and the National Water Resources Policy, which defines water as a public good and recommends a decentralized management process, guided by environmental governance, with the participation of public authorities, users and communities, aiming at strengthening the committees, including in the decision-making processes. Silva et al (2016) reported that, although legally ensured, transparency and social control in public health are often not observed in a practical way, and that many public sector contracts with private service providers are not properly presented to interested citizens.…”
Section: Figurementioning
confidence: 99%
“…Williamson & Kerekes (2011) stated that informal institutions are powerful in protecting the right to property, even superior power to formal institutions. The research found that there were understandings about the problems of the Cantareira System, especially assimilated during the biggest crisis of the system (2013-2015), reported almost daily in local, regional and national media (Martirani & Peres, 2016). However, these have been limited to make producers aware that the way they deal with natural resources on their properties affects the supply of millions of people.…”
Section: The Management Of Natural Resources In Private Propertiesmentioning
confidence: 99%
“…Assessing water quality has become increasingly concerning and relevant for several river basins, including the southeastern Amazon, Brazil [19][20][21]. The northern region still lacks water quality monitoring and surveillance records [22].…”
Section: Introductionmentioning
confidence: 99%